Alterações hemodinâmicas maternas e a sua repercussão na homeostase fetal em gestantes hígidas submetidas a esforço físico aeróbico - Santos, Caroline Mombaque dos (2015)
Introduction: Physical activity and reproduction are part of the life context of a healthy woman and a combination of regular exercise during pregnancy seems benefits to the mother and the fetus in almost ways. A public health argument is that women who start in pregnancy exercises tend to continue. Justification: medical community may have studies about the security for guidance as to the exercise in pregnancy. Purpose: To evaluate maternal hemodynamic changes in low-risk pregnant women submitted to aerobic physical effort and its impact on fetal vitality. Methodos: the tests were performed at the Exercise Physiology Laboratory and Human Performance at CEFD / UFSM. The study of quasi-experimental design consisted of pregnant women obtained by sample of convenience, low risk with GA between 26 and 34 weeks, volunteers. The TCL was applied to all participants. On arrival at the laboratory, the research subjects were placed in semi-Fowler position in the left lateral decubitus, obtained rest CTG for a period of 20 minutes, measured the PA and maternal FC. The US was then performed and after obtaining the rest of data - place I (PBF, umbilical artery Doppler indices, middle cerebral, uterine artery and ductus venosus), the participant will perform the session. All patients were submitted to a progressive exercise test according to Balke and Ware protocol. Immediately after the exercise test, return to semi-Fowler position in the left lateral decubitus when it will submit again to biophysical tests and dopplermetria (place II). The GA in delivery, mode of delivery, birth weight, Apgar scores were obtained from birth records. For the distribution of independent variables used the descriptive analysis. We used the paired Student t test to assess the values of Doppler after logarithmic transformation of the data that did not follow the normal. A 5% significance level was considered satisfactory, and data storage and analysis in SPSS version 21.0. Results: We performed 28 samples, with a mean maternal age of 26 ± 6.97 years and average GA in data collection time of 30.51 ± 3.36 weeks and childbirth 39.01 (± 0.95) weeks. There was no change in the CTG, PBF, Doppler indices of ACM, uterine artery and ductus venosus after the stress test. Identified change in RI (p = 0.02) and IP (p = 0.01) after exercise umbilical artery. There was no linear growth of maternal hemodynamic parameters in relation to items on the Borg Scale. Conclusions: we identified that although treadmill exercise test, the healthy fetus develops compensatory mechanisms that maintain homeostasis in healthy and previously sedentary pregnant women. So monitored exercise did not bring negative repercussions for pregnancy, confirming the safety of the activity during the pregnancy period and that the results can be extrapolated to similar populations.